Interaction of Two-phase Debris Flow with Lateral Converging Shear Walls - Kattel, Parameshwari; Tuladhar, Bhadra Man (Journal of Nepal Mathematical Society, 2018)
Landslides, debris avalanches and debris flows are common mass wasting phenomena in mountain slopes. Debris flows can increase their volume and destructive potential by scouring undermining banks, thereby bringing morphological changes. Construction of lateral shear walls as embankments is a way of mitigation. In natural debris flows, solid and fluid evolve dynamically differently and show different inter-action with obstacles. So, we employ a general two-phase mass flow model (Pudasaini, 2012) consisting of a set of highly non-linear and hyperbolic-parabolic PDEs for mass and momentum balances for both downslope and cross-slope directions. Besides buoyancy, the model includes the dominant physical aspects of the flow: virtual mass force, generalized drag and non-Newtonian viscous stress. Our numerical experiments show that the solid is more obstructed than the fluid when a debris flow passes over a system of converging lateral shear walls resulting in different flow-dynamics, wall-interactions and run out morphology of the phases. Narrower the slit, more is the obstruction. Solid component is more obstructed than the fluid, resulting in a phase-separation. The obstruction is related with the contraction ratio due to the converging shear walls. These computations and the observations increase our understanding of the flow dynamics and interactions with the lateral shear walls. The results may be extended further to achieve some engineering solutions to hazard mitigation in debris-flow prone zones.